EXCELLENCE MANAGEMENT: STRATEGIES TOWARD ‘SCHOOL AS A LEARNING COMMUNITY’ FOR SECONDDARY SCHOOLS - พิบูลวิทิตธำรง, จิณณภัทร (Pathumthani University Academic Journal, 2022)
The purpose of the article is to present the concept of school development as a learning community. It can lead to organizational management to excellence at the secondary school level as a result of the research study on the management strategy of excellence in secondary schools to become a learning community of the authors. By starting with 1) School as Learning Community concept in foreign countries and in Thailand 2) School components as learning community and characteristics of school as learning communities. 3) External contexts of secondary school administration. Policy and administration of secondary schools under the Office of the Basic Education Commission. 4) Excellence in Secondary School Management under the Office of Basic Education Commission Quality Award (OBECQA) and 5) Defining strategies for managing excellence of secondary schools to become a community of learning. Excellence management strategies for secondary schools towards school as a learning community consists of 6 strategies: 1) Transform the development of teachers and educational staffs’ capacity towards the vision and philosophy of school as a learning community, 2) Transform the development of school principals’ paradigm on vision and philosophy of school as a learning community, 3) Transform the relationship and engagement with learners and stakeholders to enhance participation in education reform in schools based on the philosophy of school as a learning community, 4) Develop management, analysis, and knowledge management system following the philosophy and activities of the school as a learning community, 5) Develop teachers’ mindset and performance consistent with the philosophy and activities of school as a learning community, and 6) Continue developing the strategic plans in line with the vision of the school as a learning community.